Application of the Hadith Study Methodology Hisbah Council of the Persatuan Islam - Siti Mirah Nuraeni; Tajul Arifin (al-Afkar, Journal For Islamic Studies, 2025)
Background: The Dewan Hisbah serves as a fatwa and research institution responsible for ensuring that the understanding of Hadith aligns with Sharia principles and can be applied contextually in the lives of Muslims. Purpose of the Study: To understand the methodology of Hadith study implemented by Dewan Hisbah of Persatuan Islam in assessing the authenticity and relevance of Hadith as a basis for issuing fatwas, and to explore the contribution of Dewan Hisbah's application of Hadith study methodology to the development of understanding and implementation of Islamic teachings among Muslims. Methods: The research titled Application of the Hadith Study Methodology of Dewan Hisbah of Persatuan Islam employs a literature review as the primary approach. Literature collection was conducted using two main platforms, PubMed and Google Scholar, with keywords such as "application of methodology," "Hadith Dewan Hisbah," and "Persatuan Islam." Results: The application of the Hadith study methodology by Dewan Hisbah has bridged the gap between the tradition of Islamic scholarship and the needs of the Muslim community in the modern social context. Conclusions: This role not only maintains the relevance of Islamic teachings but also fosters the creation of a civilized society based on universal and inclusive Sharia values.